PERAN DEWAN PENGAWAS SYARIAH (DPS) DALAM PENERAPAN TATA KELOLA BPRS - ABDUL AZIZ, UMAR; MUBARAK, JAIH; SUSANTO, HARI (Universitas Ibn Khaldun Bogor, 2023)
The enforcement of sharia compliance in LKS has not run optimally, even though sharia compliance can affect customer satisfaction. One of the determinants of the success of implementing sharia compliance in LKS is the Sharia Supervisory Board (DPS). This study aims to determine the role of DPS PT. BPRS XXX in Bogor Regency and DPS PT. BPRS YYY in Cianjur Regency in implementing the governance of BPRS POJK Number 24/POJK.03/2018. This type of research is a field research with a qualitative approach. The results of this study are that DPS BPRS XXX and BPRS YYY have carried out their roles well even though there are several tasks that are not in accordance with OJK regulations, such as mentioning the reasons for taking samples, not explaining concurrent positions and remuneration in detail in the governance report. From the results of the assessment of the role of DPS in the two BPRS, BPRS XXX is slightly superior to BPRS YYY because BPRS YYY has one transaction that is not sharia-compliant. In the Implementation Scale of DPS Governance, both BPRS received good predicate. Recommendations in this study include for DPS in addition to knowing the sciences of fiqh muamalah, DPS also needs to know the ins and outs of the transaction flow in LKS. In addition, DPS also needs to know statistics so that the inspection of documents by sampling is more accurate and represents other documents that were not examined.